Beta-Carotene, Anthocyanin, Antioxidant Activity, and Microbiological Quality of Steamed Sponge Cakes for Alternative Post-Disaster Snack Food - Rahman, Nurdin; Ariani, Ariani; Rakhman, Aulia (Media Publikasi Cendekia Indonesia, 2025)
The research aims to analyze the levels of beta carotene, anthocyanin, antioxidant power (IC50), and yeast numbers of steamed sponge cake mold based on a combination of purple sweet potato flour (Ipomoea Batatas L.) and orange sweet potato flour (Ipomoea Batatas L.) as an alternative post-disaster snack. The type of research was a Factorial Completely Randomized Design (CRD) using a ratio of wheat flour and a combination of purple sweet potato flour and orange sweet potato flour, namely 100:0 (F0), 80:20 (F1), 70:30 (F2), 60: 40 (F3), and 50:50 (F4). Data analysis included beta carotene, anthocyanin, IC50 of antioxidant activity, and mold yeast numbers. The steamed sponge cake with the highest anthocyanin content is formula F4 (2.64 mg/100 g), followed by formula F3 (1.57 mg/100 g). The β-carotene levels (mg/100g) show that the F3 formula is the highest, at 38.83 mg/100 g, and the F2 formula is 29.33 mg/100 g. The most potent antioxidant power is the F4 formula of 91.84 µg/mL. Formula F4, at a dilution of 10-6, obtained the lowest yeast number, 7 CFU/mL. Formula F4 is the best formula of the four formulas tested. Formula F4 has high levels of anthocyanin, β-carotene, antioxidant power, and the lowest number of yeast molds.